2004
DOI: 10.1542/peds.2004-0436
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Autoimmune Multiorgan Syndrome (Paraneoplastic Pemphigus) in a Child: Case Report and Review of the Literature

Abstract: ABSTRACT. Paraneoplastic autoimmune multiorgan syndrome, also known as paraneoplastic pemphigus, has been observed only rarely among children. We describe a 10-year-old boy with typical clinical and histologic findings of paraneoplastic pemphigus associated with Castleman's disease. His disease was refractory to resection of the tumor and aggressive combination immunosuppressive therapies. The patient died 1 year after presentation, as a result of complications of bronchiolitis obliterans. This case is unusual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 28 publications
(26 reference statements)
0
40
0
1
Order By: Relevance
“…( 73 The stomatitis may be initially mistaken for HSV or StevensJohnson Syndrome (SJS) and a paraneoplastic workup may not initially be considered especially in pediatric patients. 74 The course can be complicated by bronchiolitis obliterans, respiratory failure, and death.…”
Section: What Are the Differences Between Pemphigus Vulgaris In Childmentioning
confidence: 99%
See 1 more Smart Citation
“…( 73 The stomatitis may be initially mistaken for HSV or StevensJohnson Syndrome (SJS) and a paraneoplastic workup may not initially be considered especially in pediatric patients. 74 The course can be complicated by bronchiolitis obliterans, respiratory failure, and death.…”
Section: What Are the Differences Between Pemphigus Vulgaris In Childmentioning
confidence: 99%
“…Progression and death occurred despite treatment of the underlying malignancy or with immunosuppressive therapy for PNP. Unlike adults, they found that the skin findings in the pediatric patients tended to be more lichenoid and less blistering.Treatment of PNP includes treatment of the malignancy and palliative immunosuppression which canlead to remission of the blistering disease, butoften in this ominousdisease the ultimate prognosis remains poor 73,76,80,81. Although no evidence based treatment recommendations are available, there is a report suggesting that early recognition and removal of a Castleman's tumor as well as peri-operative IVIG may mitigate the risk of subsequent bronchiolitis obliterans.…”
mentioning
confidence: 99%
“…Ogawa et al reported that the mean age of onset in his series was 64.7 [7] . However, PNP can affect every age group, including children and adolescents [8][9][10] . PNP appears to affect males and females equally [2] .…”
Section: Epidemiologymentioning
confidence: 99%
“…In contrast, if cell-mediated cytotoxicity is the leading mechanism, lichenoid lesions might be easily seen [33,35,36] . Lichenoid lesions are commonly detected in children, especially on the trunk and limbs [9,10] . Lesions resembling those of pemphigoid are usually present on the extremities [45] .…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation